Performance of a new model of nasal filter when challenged against PM1 aerosols. Issue 1 (1st January 2021) - Zhu, Jintuo; Jing, Pengli; Hao, Yaxin; He, Xinjian; Wang, Liang; Zhang, Ruxue; Liu, Jinyu
ABSTRACT: Nasal filters are increasingly used in reducing personal haze exposures, but there is no retrievable evidence on its efficiency. In this study, a nasal filter testing system was designed. NaCl aerosols were generated to simulate PM1. Three different sizes of a new model of nasal filter were tested under two flow types (constant vs. cyclic) and three flow rates (15, 30, and 50 L/min). All PM1 penetration values were > 80%. Either enlarging filter size or lowering flow rate significantly reduced PM1 penetration, and PM1 penetration under cyclic flow was significantly higher compared with constant flow. To avoid mouth breathing, nasal filters could only be worn under light work-rates or rest conditions. The quality factor of nasal filters was only hundredths that of the N95 and P100 FFRs. This study reveals that there is a future need to design nasal filter materials with higher efficiency and lower flow resistance.